Android Mobile Learning Raises Motivation Higher Than Learning Outcomes: Mobile Learning Android Meningkatkan Motivasi Lebih Tinggi dari Hasil Belajar - Ai Siti Hodijah; Andang Sunarto; wiwinda wiwinda (Indonesian Journal of Innovation Studies, 2026)
General Background: The integration of information and communication technology in education has transformed learning into a more interactive and flexible process, positioning mobile learning as a strategic approach in the digital era. Specific Background: The increasing use of smartphones among elementary students has shifted attention toward non-academic activities, leading to decreased motivation and suboptimal learning outcomes in religious education subjects. Knowledge Gap: Prior studies predominantly focus on higher education levels and general subjects, leaving limited empirical evidence on Android-based mobile learning in elementary religious education contexts. Aims: This study examines the relationship between Android-based mobile learning usage, student learning motivation, and cognitive learning outcomes. Results: The findings indicate a significant relationship between mobile learning and learning motivation with a determination coefficient of 46.4%, while its relationship with learning outcomes is significant but relatively low at 4.2%. Novelty: The study provides simultaneous analysis of mobile learning, motivation, and cognitive outcomes in elementary religious education, offering a more integrated perspective compared to prior research. Implications: The results highlight the need for combining mobile learning with appropriate instructional strategies, teacher guidance, and supportive learning environments to achieve more balanced educational outcomes. Highlights• Mobile learning shows stronger contribution to student engagement compared to cognitive achievement• Digital integration supports active participation and flexible access to learning materials• Learning outcomes remain shaped by multiple external educational factors KeywordsMobile Learning; Android Learning; Learning Motivation; Learning Outcomes; Elementary Education